2003
DOI: 10.2134/jeq2003.1183
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide Volatilization from Soil

Abstract: A comparison was drawn between model predictions and experimentally determined volatilization rates to evaluate the volatilization approaches of European registration models. Volatilization rates of pesticides (14C-labeled parathion-methyl, fenpropimorph, and terbuthylazine and nonlabeled chlorpyrifos) were determined in a wind-tunnel experiment after simultaneous soil surface application on Gleyic Cambisol. Both continuous air sampling, which quantifies volatile losses of 14C-organic compounds and 14CO2 separ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…The volatilization kinetics of the fungicide fenpropimorph expresses a clear corre lation between volatilization mtes and soil moisture content. Volatilization mtes reached a maximum 24hr 978-1-4244-7388-5/10/$26.00 ©201O IEEE 347 after application under moist conditions and decreased with the decrease in soil moisture over following days [9]. Li studied the effect of moisture content on the volatilization of diesel oil in soils.…”
Section: Introductionmentioning
confidence: 99%
“…The volatilization kinetics of the fungicide fenpropimorph expresses a clear corre lation between volatilization mtes and soil moisture content. Volatilization mtes reached a maximum 24hr 978-1-4244-7388-5/10/$26.00 ©201O IEEE 347 after application under moist conditions and decreased with the decrease in soil moisture over following days [9]. Li studied the effect of moisture content on the volatilization of diesel oil in soils.…”
Section: Introductionmentioning
confidence: 99%
“…It incorporates the effect of prevailing meteorological conditions on the initial estimation of pesticide volatilisation from crops in the field. PELMO estimates volatilisation from soil water by assuming negligibly low concentration of pesticide in the air above the soil (not including soil-air partitioning) (Wolters et al 2003). Other competing processes for dissipation of pesticides in different environmental compartments were not included in our calculations so that leaching, transformation and wash-off from plant surfaces were all excluded, creating a more protective risk assessment.…”
Section: Methodsmentioning
confidence: 99%
“…Algorithms from PELMO were used in the estimation of pesticide emission rates from exposed soil surfaces on a daily basis (Wolters et al 2003; Ferrari et al 2005): …”
Section: Methodsmentioning
confidence: 99%
“…Extensive researches have been conducted on the chlorpyrifos' detection methods, toxic effects [1], transformation, and degradation processes of chlorpyrifos in water and soil [9,10]. It was reported that atmosphere is a major receptacle and transport medium for pesticides through their spraying, volatilization, or wind erosion of soil particles and dusts which are loaded with pesticides [11][12][13][14][15][16]. Chlorpyrifos is a potential long-range transport pesticide in the atmosphere [17].…”
Section: Chlorpyrifosmentioning
confidence: 99%